Internalization of The Values of Tolerance and Togetherness in The Practice of The Rebo Wekasan Tradition - Qiptiyah, Titin Mariatul; Arifin, Zainal; Rizal, Syaiful (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The Rebo Wekasan tradition in the Sundoan community of Jember is a syncretic blend of religious rituals and local culture, believed to ward off disaster on the last Wednesday of the month of Safar. This study aims to examine how the core rituals of this tradition, particularly the provision and distribution of ketupat (rice cakes) and the performance of special sunnah prayers, serve as a means of internalizing the values ​​of tolerance and togetherness within a diverse community. This research uses a qualitative case study approach, with triangulation techniques for data validation. Data analysis employs an interpretive-descriptive approach to understand the symbolic meaning and social function of these traditional practices. The practice of Rebo Wekasan in Sundoan, Jember, effectively fosters social values. The ritual of sharing ketupat (or ketupat to ward off disaster) serves as a unifying symbol that embodies togetherness (ukhuwah) as all residents share the same food, regardless of status or background. Furthermore, the collective voluntary prayers strengthen spiritual solidarity. Interestingly, the diversity of religious views on these prayers does not lead to conflict but is instead addressed through tolerance and mutual respect, embracing differences as a communal asset. The research results show that the Rebo Wekasan tradition effectively transforms individual beliefs about warding off disaster into collective social action. This is achieved through the ketupat symbol and the practice of communal sunnah prayers. This ritual serves a dual function: as an expression of religion and culture, as well as a social mechanism to maintain tolerance and strengthen togetherness (social cohesion) among residents in the Sundoan community of Jember